Temperature and Host Fruit During Immature Development Shape Adult Life History Traits of Different Ceratitis capitata Populations - Georgia D. Papadogiorgou; Nikos T. Papadopoulos (Insects)
Temperature and host fruit availability are key factors influencing the life history traits of the Mediterranean fruit fly (medfly) (Ceratitis capitata). This study examines how developmental temperature and host fruit type affect adult longevity and fecundity in medflies from six populations spanning Southern to Central Europe. Larvae were reared on apples and bitter oranges at three constant temperatures (15, 20, and 25 °C), with pupae maintained under the same thermal conditions until adult emergence. Adults were then kept at 25 °C, with longevity and fecundity recorded daily. The results showed that higher developmental temperatures increased adult lifespan across all populations, regardless of host fruit. Similarly, fecundity rates in ovipositing females were higher at higher temperatures. Reproductive periods (pre-oviposition, oviposition, and post-oviposition) varied among populations, indicating population-specific responses. These findings underscore how temperature and host fruit availability shape medfly invasion dynamics, highlighting the species’ biological plasticity and adaptation to different environments. This research provides valuable insights for pest management, particularly in the context of climate change, offering strategies to mitigate the spread of medflies into new regions.